FISEA - Fourth International Symposium on Electronic Art : Abstract and Artist Statements. - Apostolos, Margo K.; Ascott, Roy; Barilleaux, René Paul; Beyls, Peter; Claus, Jürgen; Evans, Brian; Gigliotti, Carol; Gold, Rich; Halaby, Samia A.; Harris, Craig; Herman, Martin; Hoet, Jan; et al. (Minneapolis : Minneapolis College of Art and Design, 1993)
Abe, Yoshiyuki ; Acevedo, Victor ; Arntson, Amy E. ; Badger, Paul ; Bessa, Romeu ; Bradley, Steve ; Breiger, Elaine ; Brill, Bob ; Cash, Sydney ; Chmelewski, Kathleen ; Dale, Denis A. ; Davies, Char ; Davison, Bill ; Dehlinger, Hans ; Dickson, Stewart ; dimon, Roz ; Farber, Leslie Nobler ; Fenster, Diane ; Flax, Carol ; Fraga, Tania ; George, Phillip ; Gleeson, Madge ; Holzer, Steve ; Husom, David ; Kac, Eduardo ; Krause, Dorothy Simpson ; Merrill, Lizanne ; Mosher, Michael R. ; Mühleck, Georg ; Munzner, Aribert ; Murphy, Jeff ; Rose, Ann-Marie ; Seaman, Bill ; Shapiro, Bruce ; Sherman, John F. ; Smith, Rosemary ; Sun, Chingyu ; Tonkin, John ; Traube, Alex Fernandez ; Tremblay, Pierre ; Truckenbrod, Joan ; Vicente, Carlos Fadon ; Faure Walker, James ; Weintraub, Annette ; Wilson, Mark ; Zahulka, Anne
Fisea '93 : The Art Factor - Fourth International Symposium on Electronic Art : Papers, Minneapolis, Minnesota U.S.A., November 3-7, 1993
Engels
boek